Discovery of highly functionalized 5, 6-seco-grayanane diterpenoids as potent competitive PTP1B inhibitors. Issue 6 (13th February 2020) - Zhou, Junfei; Zuo, Zhili; Liu, Junjun; Zhang, Hanqi; Zheng, Guijuan; Yao, Guangmin
Abstract : Three competitive PTP1B inhibitory diterpenoids with a 5, 6- seco -grayanane carbon skeleton (1–3 ) were isolated and identified from Rhododendron molle . A more potent competitive PTP1B inhibitor (9 ) was designed and prepared based on a docking study. Abstract : Protein tyrosine phosphatase 1B (PTP1B) is an important therapeutic target for type II diabetes mellitus. Mollactones A–C (1–3 ), three naturally occurring highly functionalized 5, 6- seco -grayanane diterpenoids bearing a unique 3-oxa-tricyclo[4, 3, 2, 0 2, 6 ]undecane motif, and their plausible biosynthetic precursor rhodojaponin III (4 ) were isolated from Rhododendron molle . The 13 C NMR spectrum of 1 exhibited only 11 carbon signals, instead of 20 carbon signals, and this challenging structure was finally defined by single-crystal X-ray diffraction analysis. This abnormal NMR phenomenon was elucidated by quantum chemical calculation. Mollactones A–C (1–3 ) showed significant PTP1B inhibitory activity in a competitive inhibition mode, and their structure–activity-relationships were investigated. Based on the molecular docking studies, mollactone B 3- O -sulfate (9 ) was rationally designed and prepared, and exhibited significant PTP1B inhibitory activity with an IC50 value of 0.22 ± 0.05 μM and a K i value of 6.79 ± 1.28 μM. These results provide a basis to design novel competitive PTP1B inhibitors based on 5, 6- seco -grayanane diterpenoids with 3-oxa-tricyclo[4, 3, 2, 0 2, 6 ]undecane and 5, 5-dimethylcyclopent-2-en-1-one motifs.